Hemorrhagic Stroke - An Update - Amit Agrawal (IntechOpen, 2017)
The present book Hemorrhagic Stroke - An Update includes the updated information for professionals who are involved in the management of spontaneous intracerebral hemorrhage. This book contains detailed information about the pathophysiology of spontaneous intracerebral hemorrhage, neuroimaging approach in intracerebral hemorrhage, how to go about surgical intervention decision-making in these patients, and the rehabilitation issues in acute care and in long-term survivors. I hope that the collective contribution from the experts will make this book a valuable guide to further develop their understanding about spontaneous intracerebral hemorrhage. I am grateful to all the authors who have contributed their tremendous expertise to the present book and to my wife and daughter for their passionate support, and last but not least, I wish to acknowledge the outstanding support of Ms. Romina Skomersic, Publishing Process Manager, InTech Open Science, Croatia, who collaborated tirelessly in crafting this book.
English
Keywords: Medicine; Hematology; Hemorheology; Health Sciences